Um triente de égica em Aquae Flaviae - Guedes, César (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
A VIIth century tremissis struck in Emerita during the sole reign of Egica (c. 687-698) is reported. The coin was found in 2007 during an archaeological excavation in the city of Chaves (Vila Real, Portugal). The author also refers other coins issued by this king with known geographical provenience.